2022
DOI: 10.1016/j.cegh.2021.100953
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to donate blood and associated factors among patient caregivers at the University of Gondar Comprehensive Specialized Hospital, northwest Ethiopia

Abstract: Background: Ethiopia is one of the countries with a significant shortage of medical blood. Patient caregivers can serve as an important pool of potential blood donors for many reasons. However, limited data are available on the willingness of patient caregivers to donate blood in Ethiopia. Therefore, this study assessed patient caregivers' willingness to donate blood and associated factors in northwest Ethiopia. Methods: An institution-based cross-sectional study was conducted among 342 patient caregivers at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Most of the participants in the present study were of age group 30-39 years (54.4%). This was at variance with other studies in Ethiopia [22][23][24] and other parts of Nigeria [25,26] where younger age groups constituted most of the study participants whereas In Osogbo, [27] Nigeria older age groups predominated. The reason for this difference could not be ascertained other than variation in the age groupings in the various studies.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Most of the participants in the present study were of age group 30-39 years (54.4%). This was at variance with other studies in Ethiopia [22][23][24] and other parts of Nigeria [25,26] where younger age groups constituted most of the study participants whereas In Osogbo, [27] Nigeria older age groups predominated. The reason for this difference could not be ascertained other than variation in the age groupings in the various studies.…”
Section: Discussioncontrasting
confidence: 89%
“…This was surprisingly low as almost all the participants (92.5%) knew that blood transfusion was a life-saving procedure. Higher percentages of 73.9%, 78.1% and 85.5% were reported by Oluomachi et al, [25] Kebede et al [22] and Melku et al [23] in Ebonyi state and Ethiopia respectively. In contrast, Melku et al [8] in another study in Ethiopia reported that only 46.4% participants were willing to donate blood voluntarily within the coming 6 months.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…As a result of the literature review, a 14-question form was created by the researchers (Suluhan et al, 2016;Kebede et al, 2022). The form includes four socio-demographic characteristics (age, gender, marital and educational status) and ten questions on determining knowledge, attitudes, and behaviors about immune plasma donation.…”
Section: Data Collection Toolsmentioning
confidence: 99%